Because Claudette - Baptiste, Tracey; Engel, Tonya (New York : Dial Books for Young Readers, 2022)
A picture book about Claudette Colvin, the teen whose activism launched the Montgomery bus boycott, and a celebration of collective action.
Includes bibliographical references.
K-3.
Keywords: Colvin, Claudette, -- 1939- -- Juvenile literature; African American teenage girls -- Alabama -- Montgomery -- Biography -- Juvenile literature; African Americans -- Alabama -- Montgomery -- Biography -- Juvenile literature; Montgomery Bus Boycott, Montgomery, Ala., 1955-1956 -- Juvenile literature; Segregation in transportation -- Alabama -- Montgomery -- History -- Juvenile literature; Montgomery (Ala.) -- Race relations -- History -- 20th century -- Juvenile literature; Colvin, Claudette, -- 1939-; African Americans -- Biography; Teenage girls; Montgomery Bus Boycott, Montgomery, Ala., 1955-1956.; Segregation in transportation -- History; Montgomery (Ala.) -- Race relations -- History -- 20th century; Protest movements -- Juvenile fiction; Biographies